2011
DOI: 10.1016/j.matdes.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of magnesium spot welds under tensile and cyclic loadings

Abstract: Resistance spot welds of a magnesium alloy were characterized in terms of microstructure, hardness and monotonic and cyclic properties. Microstructural features in base metal and different zones in the weld region were discussed and the mechanical behavior of spot welds in tensile-shear configuration was studied. Effects of welding parameters were investigated on the micro-and macroscale characteristics of magnesium spot welds. To this end, five sets of spot weld specimens were prepared, utilizing different we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…Nugget sizes were measured after monotonic testing as the average diameters of the bonding area, along and perpendicular to the loading direction. The work by Behravesh et al [16] provides a detailed discussion of the effect of process parameter on static and fatigue performance of Mg spot-welds.…”
Section: Materials and Specimensmentioning
confidence: 99%
See 3 more Smart Citations
“…Nugget sizes were measured after monotonic testing as the average diameters of the bonding area, along and perpendicular to the loading direction. The work by Behravesh et al [16] provides a detailed discussion of the effect of process parameter on static and fatigue performance of Mg spot-welds.…”
Section: Materials and Specimensmentioning
confidence: 99%
“…This ratio in the work by Sheppard et al [36] is 30%. Another deficiency associated with the fracture mechanics approach is that the formulations are based on the assumption that the crack is along the faying surface; however, it has been shown that through-thickness cracking is more common for TS specimens [16,26,27,31].…”
Section: Fracture Mechanics Approach -Swellam's Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…However, limited studies are available on fatigue of Mg/Mg similar spot welds. Behravesh et al . investigated the fatigue behaviour of magnesium spot welds with different nugget sizes.…”
Section: Introductionmentioning
confidence: 99%